Angiosarcoma of the scalp - Manjiri DasGupta; Nilay Chakrabarti; Pravin Agrawal; Swati Narurkar (Indian Journal of Plastic Surgery)
Angiosarcoma is a relatively rare soft tissue tumour. It usually occurs in the head and neck, and especially in the scalp, in elderly people. Its presentation varies from a small plaque to multifocal nodules. The treatment depends on the extent of the disease. Most cases are treated with wide excision with reconstruction. Radiotherapy and chemotherapy are advocated in the recurrent or extensive lesions with regional or distant metastasis. Other modalities such as immunomodulation have been tried. A case of a 55-year-old female patient with a bleeding scalp lesion is presented. Initially thought to be a pyogenic granuloma, on excisional biopsy it was diagnosed as angiosarcoma with microscopic involvement of the margins. Wide excision with reconstruction using a local rotation flap was done at a second stage. The patient was not given postoperative radiotherapy or chemotherapy. There has been no recurrence for two years.